Functional Characterization of PtoWOX1 in Regulating Leaf Morphogenesis and Photosynthesis in Populus tomentosa - Feng Tang; Minghui He; Shi Liang; Meng Zhang; Xiaowei Guo; Yuxian Dou; Qin Song; Cunfeng Zhao; Ting Lan (Plants)
Leaves are essential for photosynthesis and transpiration, directly influencing plant growth and development. Leaf morphology, such as length, width, and area, affects photosynthetic efficiency and transpiration rates. In this study, we investigated the role of PtoWOX1 in leaf morphogenesis by generating both overexpression and CRISPR/Cas9 knockout lines in P. tomentosa. The results showed that PtoWOX1A and PtoWOX1B encode nuclear-localized transcription factors highly expressed in young leaves, particularly in palisade and epidermal cells. Knockout of PtoWOX1 resulted in reduced leaf width and area, enlarged upper epidermal cells, and lower stomatal density. Overexpression led to wrinkled leaf surfaces and reduced margin serration. Anatomical analysis revealed altered palisade cell arrangement and increased leaf thickness in knockout lines, accompanied by higher chlorophyll content and enhanced photosynthetic rates. Additionally, PtoWOX1A interacts with PtoYAB3B, suggesting a complex that regulates leaf margin development. These findings clarify the function of PtoWOX1 in regulating mid-lateral axis development and leaf margin morphology and provide new insights for the molecular breeding of poplar.